A structural equation model to predict pre‐exposure prophylaxis acceptability in men who have sex with men in Leicester, UK. Issue 1 (30th August 2018) - Jaspal, R; Lopes, B; Bayley, J; Papaloukas, P
Abstract : Objectives: Pre‐exposure prophylaxis (PrEP) is an effective HIV prevention tool for high‐risk men who have sex with men (MSM). However, acceptability and uptake have been variable. This study explored the factors that predict PrEP acceptability in MSM in Leicester, where HIV prevalence is double the national average. Methods: A total of 191 HIV‐negative MSM completed a cross‐sectional survey. Participants provided demographic information, and completed measures of HIV knowledge, perceived HIV risk, engagement in sexual risk behaviour, acquisition of a sexually transmitted infection (STI) in the last 12 months, frequency of HIV testing and PrEP acceptability. Results: Kruskal–Wallis tests showed statistically significant effects of sexual orientation, education level and income, respectively, on HIV knowledge. Gay‐identified individuals possessed greater HIV knowledge than bisexuals. Respondents with General Certificate of Secondary Education (GCSE)‐level education had significantly less HIV knowledge than those educated to postgraduate level. Respondents with income of < £10 000 possessed significantly less HIV knowledge than higher income groups. Structural equation modelling showed that the relationship between HIV knowledge and PrEP acceptability was mediated by perceived HIV risk, engagement in sexual risk behaviour, acquisition of an STI in the past 12 months and frequency of HIV testing. Conclusions: The results reveal socio‐economic inequalities in HIV knowledge and HIV testing, and suggest that MSM who have high levels of HIV knowledge and perceived HIV risk and who regularly test for HIV are most likely to endorse PrEP as personally beneficial. HIV knowledge and accurate risk appraisal should be promoted in MSM. The HIV testing context constitutes an ideal context for promoting PrEP to high‐risk MSM.